PENGARUH CUSTOMER PERCEPTION DAN ATRIBUT HOTEL KAPSUL TERHADAP KEPUTUSAN MENGINAP DI BOBOBOX KOTA BANDUNG - Rino Sugiyanto, - (2023)
This study aims to describe the customer perception and hotel attributes and how to describe the purchase decision. The relationship between customer perception variables and hotel attributes on purchase decisions is one of the objectives of this study. The object of this research is the Bobobox Capsule Hotel in Bandung City and the type of research used is descriptive and verification and the method used is an exploratory survey. The sample used for research needs is a total of 97 respondents who will stay or visit the Bobobox Capsule Hotel in Bandung. To assist in proces the author's data using the help of the SPSS 25 for windows application. Based on the test, the results show that there is a simultaneous influence between customer perception and hotel attributes on purchase decisions. Partially, there is also an influence between the customer perception variable and the hotel attribute on the purchase decision.